The Potential Benefits of N2 Gas Flushing Technology for Various Dairy Products: A Sustainable Approach That Proved to Be Multiadvantageous for Preserving the Quality and Safety of Raw Milk During Its Storage - Munsch-Alatossava, Patricia; Alatossava, Tapani (Frontiers in Sustainable Food Systems, 2021)
Worldwide, food production systems are confronted with multifaceted challenges. In the context of global climate change, the necessity to feed an expanding population while addressing food insecurity and reducing the tremendous losses and wastage of food places all production steps under considerable pressure. In this context, dairies also face extensive pressure to reduce GHG emissions, wastewater, and sludge; here, as elsewhere, innovative technological solutions must meet sustainable criteria. To preserve the quality and safety of raw milk during its storage, N2 gas flushing technology was devised and implemented at laboratory and pilot plant scales: the treatment proved to be multiadvantageous considering microbiological, biochemical and technological aspects. The proposed review aims to reconsider the benefits of the patented N2 flushing technology, applied at the “raw milk stage”, and evaluate the potential advantages that the treatment would confer, in terms of quality and safety aspects, to various dairy products such as liquid milk products, butters, creams, ice creams, and cheeses, including local and traditional dairy products.